2015
DOI: 10.17795/ajdr-24038
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography Study of Root and Canal Morphology of Maxillary first Molar in an Iranian Population

Abstract: Background:The success of endodontic treatment depends on detection of all root canals so that they could be cleaned, shaped and obturated appropriately. To achieve this, it is essential to know root canals complexities such as the number of canals and types of each root canal, which are genetically determined. Besides, the highest failure rates occur in maxillary first molars. Objectives: Therefore, the aim of this study was to investigate the root and canal morphology of maxillary first molars in an Iranian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In our study, there was a male preponderance in the prevalence of root canal variations (Figures 3 and 4) (p=0.002, statistically signi icant). This inding is in concordance with the previous study held among the Iran population, shows that the male patients show more deviation in the root canal anatomy (Faramarzi, 2015;Hosseinpour, 2016).…”
Section: Resultssupporting
confidence: 93%
“…In our study, there was a male preponderance in the prevalence of root canal variations (Figures 3 and 4) (p=0.002, statistically signi icant). This inding is in concordance with the previous study held among the Iran population, shows that the male patients show more deviation in the root canal anatomy (Faramarzi, 2015;Hosseinpour, 2016).…”
Section: Resultssupporting
confidence: 93%
“…The usual distance between MB1 and MB2 ranges from 1.5 to 2 mm mesially and 2.5 to 3.5 mm palatally with a maximum reported distance of 4 mm by Faramarzi et al 19 Here, the MB2 canal was located 5.607 mm away from the MB1 canal at the orifice level. Raju et al reported an unusual case of MB2 orifice located closer to the palatal orifice, but they have not mentioned the distance between MB1 and MB2 canals.…”
Section: Investigatorsmentioning
confidence: 83%
“…Some needs are met by CBCT exams, such as diagnosis, treatment planning, evaluation of intraoral pathologies, evaluation of root canal morphology and shape, evaluation of root resorption components, evaluation of the concept of obturation and assistance with the removal of root canal fillings, preoperative preparation, and evaluation of internal and external root resorption. Some research suggests that the second mesiobuccal channel of human maxillary molars may be identified using CBCT [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%